Current Challenges and Trends in Educational Tutoring - Ademola, Raziya (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
This study explores the impact of tutorial tutoring on students' academic and career success. By employing thorough methodologies such as stratified random sampling, tool validation, and various statistical analyses like paired-samples t-tests, regression, ANCOVA, and Pearson correlational analyses, important findings have been revealed. Research suggests that engaging in tutoring sessions leads to notable improvements in academic performance, especially for college students who express higher levels of satisfaction with their tutors. Regression analyses indicate that tutoring hours, satisfaction with tutors, and educational progress are significant predictors of tutorial outcomes. Recognizing limitations and self-mentioned facts, the author emphasizes the importance of quality tutoring programs in meeting academic and career needs. Future studies should investigate longitudinal and qualitative processes to gain a deeper understanding of tutoring dynamics. Concluding, the analysis supports continued investment in impactful tutoring programs to enhance student academic achievement and career preparedness.